Pengaruh Celebrity Endorser Online Shop di Instagram terhadap Minat Beli Produk Fashion Muslim dalam Sudut Pandang Syariah Marketing - Annisa Mangole (TASAMUH: Jurnal Studi Islam, 2019)
This study aims to analyze the effect of Instagram endorsement on the interest in buying Muslim fashion products and to find out how to use endorsement Instagram in the perspective of sharia marketing. There are four endorser indicators that will become research variables, namely Visibility, Credibility, Attraction and Power. The method used in the study is a quantitative method with a descriptive type of research. This research was tested by FEBI students at Sunan Kalijaga UIN by taking 100 respondents. Data collection is done by giving questionnaires using the 5-point Likert Scale. The data that has been obtained is then analyzed using the Multiple Linear Regression Test on SPSS 21. The results of the study show that only Credibility and Attraction variables partially have a positive and significant effect on the Interest in Buying FEBI Students at Sunan Kalijaga UIN. While the Visibility and Power variables are less influential. However, simultaneously the Visibility, Credibility, Attraction and Power variables have a positive and significant effect on the Students Interest in Buying FEBI at Sunan Kalijaga UIN with a determination coefficient of 0.502 or 50.2%. This means that the Visibility, Credibility, Attraction and Power variables are able to influence Purchase Interest by 50.2%, while 49.8% are influenced by other variables not included in this study. In addition, from the results of additional questions to respondents, the researchers concluded that the use of endorsers in marketing products is not yet in accordance with the characteristics of sharia marketing and not yet in accordance with ethics that are the principles of sharia marketers.